(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Cosmetic and functional gynecology is a novel specialty that is rapidly gaining traction across the globe, particularly in Europe, Asia, and America. These intricate procedures enhance the esthetics and restore the physiological function of the genitalia. This relates very closely to women sexuality, dignity, self-esteem, and overall confidence. Self-esteem is often closely mirrored and dependent on a person’s perception of her genitalia, both functionally and more recently esthetically. An increasing number of gynecologists are gradually embracing this art of restoration as the demand rapidly increases among patients. The outcomes are sometimes not pleasing to the patients and may require revision. Case series: We present four case series of undesirable outcomes from labiaplasty and perineovaginoplasty. The surgical procedures had to be repeated in two instances because of spousal demand or from the lady herself. Case 1: Reconstruction after Type IV female genital mutilation (FGM) A 46-year-old grand multipara with Type IV FGM presented with sexual dysfunction and psychosexual problems arising from FGM. She requested reconstruction of the labia minora, restoration of the labia majora, and perineovaginoplasty. Examination revealed partial clitoridectomy, a narrowed vaginal introitus with the removal of the labia minora, and excision of the labia majora. The missing tissues made the reconstruction technically difficult. Labia minora was reconstructed from the labia majora by the grooving technique, and labia majora fat augmentation with perineoplasty was performed with good outcomes. Case 2: Perineoplasty revision. A 43-year-old, para 3+0, presented with complaints of lax vaginal muscles after her third delivery. All her deliveries were normal, vertex. She sustained a second-degree perineal tear after her last delivery, which was repaired. She was started on Kegel’s exercises with no improvement. She had a perineoplasty done successfully, but she healed with a small rent. A revision was performed with good results. Case 3: Perineoplasty revision The patient underwent vaginoperineoplasty, but the perineum healed with a little bump, which both the patient and the spouse did not like. Revision of perineoplasty was performed with excellent outcomes. Case 4: Revision of an overly tight vagina after vaginoperineoplasty The patient had previously undergone vaginoperineoplasty but felt it was not tight enough. However, three months after revision, the spouse complained of incomplete penetration, whereas the patient complained of pain at the fourchette. Another revision was performed to address their concerns with good outcomes. Conclusion: Cosmetic gynecological procedures must achieve satisfactory outcomes and restore the client’s genital esthetics and functionality. Although some procedures are technically challenging and may require repeat procedures, patient satisfaction is key. Knowledge of pelvic anatomy and restoration techniques is a prerequisite for achieving acceptable outcomes. Counseling of the couple is an integral part of cosmetic gynecology to manage expectations and rule out psychosocial causes.